Computer Produced Profiles of Microtopography as a Supplement to Contour Maps - Grim, Paul J.; Keller, George H.; Barday, Robert J. (The International Hydrographic Review, 2015)
The principal products of deep sea bathymetric surveys are contour maps depicting the relatively larger features of the floor. Unfortunately, however, these maps cannot display most of the small scale features (microtopography) that are recorded on fathograms. Knowledge of this microtopography and some means of displaying it are increasingly important as man develops a greater need for utilization of the sea floor. Since future surveys are likely to be automated for data reduction, an economical and quickly produced supplement to contour maps can be computer produced profiles that clearly display the details of the bottom topography. Illustrations based on a recent narrow-beam echo sounder survey clearly point out the benefit from presenting bathymetric data in other than map form.